Blindness resulting from orbital complications of ophthalmic zoster - Moniuszko, Anna; Sosnowska, Magdalena; Zajkowska, Agata; Garkowski, Adam; Czupryna, Piotr; Pancewicz, Sławomir; Zajkowska, Joanna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Herpes zoster ophthalmicus occurs when the latent varicella zoster virus (VZV) reactivates in the trigeminal ganglion and ophthalmic branch of the trigeminal nerve. In the elderly, there is a sharp increase in the tendency of secondary skin bacterial infections occurrence due to the deterioration of capabilities of self-care and changed sanitation. We present a case of patient who developed phlegmon of the orbit, which resulted with complete unilateral blindness. Varicella zoster virus infection in the elderly may have a severe course due to the progressive weakening of the immune system related to the age. Moreover, skin lesions around the eye socket require special care in prevention of bacterial superinfections due to the extremely high risk of life-threatening complications or disability. Neuralgia resistant to pharmacological treatment present in the course of ophthalmic zoster and difficulty in caring about skin lesions predispose to the occurrence of complications.